Clinicopathological analysis of 17 primary cutaneous T‐cell lymphoma of the γδ phenotype from Japan. Issue 7 (18th June 2014) - Takahashi, Yuka; Takata, Katsuyoshi; Kato, Seiichi; Sato, Yasuharu; Asano, Naoko; Ogino, Tetsuro; Hashimoto, Kimio; Tashiro, Yukie; Takeuchi, Shogo; Masunari, Taro; Hiramatsu, Yasushi; Maeda, Yoshinobu; et al.
<x xml:space="preserve">Abstract</x> Primary cutaneous γδ T‐cell lymphoma (PCGD‐TCL) is an aggressive lymphoma consisting of clonal proliferation of mature activated γδ T‐cells of a cytotoxic phenotype. Because primary cutaneous γδ T‐cell lymphoma is a rare disease, there are few clinicopathological studies. In addition, T‐cell receptor (TCR) γδ cells are typically immunostained in frozen sections or determined by TCRβ negativity. We retrospectively analyzed 17 primary cutaneous T‐cell lymphomas of the γδ phenotype (CTCL‐γδ) in a clinicopathological and molecular study using paraffin‐embedded sections. Among 17 patients, 11 had CTCL‐γδ without subcutaneous panniculitis‐like T‐cell lymphoma (SPTCL) features and six had CTCL‐γδ with SPTCL features. Immunophenotypically, some significant differences were found in CD8 and CD56 positivity between our patient series of CTCL‐γδ patients with SPTCL features and SPTCL‐γδ patients described in the previous literature. A univariate analysis of 17 CTCL‐γδ patients showed that being more than 60 years old, presence of visceral organ involvement, and small‐to‐medium cell size were poor prognostic factors. In addition, the 5‐year overall survival rate was 42.4% for the CTCL‐γδ patients without SPTCL features and 80.0% for those with SPTCL features. Consequently, there was a strikingly significant difference in overall survival among SPTCL, CTCL‐γδ with SPTCL features and CTCL‐γδ without SPTCL features (P = 0.0005). Our data suggests that an indolent subgroup may exist in CTCL‐γδ. Studies on more cases, including those from other countries, are warranted to delineate the clinicopathological features and the significance in these rare lymphomas.